The Criminal Offence of Child-on-Child Abuse With a Fatal Outcome - Cut Firna Salsalia; Rizanizarli Rizanizarli (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2021)
This research aims to analyse the legal protection for the child offenders in criminal offence of abuse with a fatal outcome, the judge's considerations in imposing imprisonment for the offence and the obstacles in the crime. Data obtained through empirical legal research. This research uses primary data obtained from empirical legal research in the form of interviews with respondents and informants and combines legal materials such as textbooks, theories, laws and regulations which are considered as secondary data. The results of the research showed that the legal protection provided to the child convicts is in the form of identity confidentiality, is treated well during the investigation process, is placed in a special place, the Judges in making considerations always refer to the mitigating factors such as the juvenile's age, the juvenile's mental state, the juvenile's background, the juvenile's family attitude and aggravating things such as a bad juvenile's life history and parents who are unable to educate them.. The things that indirectly hinder the process of settling this case are the parents negligence, lack of cooperation from both parties, and also the influence of gadgets. It is recommended to the law enforcement officers and Juvenile’s Special Development Institute should continue to cooperate in carrying out legal protection for child perpetrators according to applicable rules, the judge before imposing a prison sentence should prioritize the best interests of the child and to parents should contributing better in control the children's behavior.